Pengaruh Model Pembelajaran Learning Cycle terhadap Kemampuan Representasi Matematis - Dewi Annisa (Departement of Mathematics Education, 2022)
Mathematical representation ability can be a bridge to understanding concepts because it can help develop and present real problems in everyday life into mathematical language. In the learning cycle itself, there are two out of five stages that can train and develop mathematical representation skills, namely the exploration and elaboration stages. In this study, the Learning Cycle learning model was used for 7th grade junior high school students to determine the effect of students' mathematical representation abilities whose learning uses the 5E Learning Cycle learning model when viewed from the student's Self Concept. The data analysis technique used two-way ANOVA and the Independent Test, as a further test. The results of this study indicate that there is a significant effect of learning cycle learning on the ability of mathematical representation in students with high self-concept. For students with low self-concept, there is no significant effect. This is because students with low self-concept tend to be happy to accept the lessons given by the teacher. Therefore, the learning cycle learning model can have effect on increasing the ability of mathematical representation in students with high self-concept.